Knowledge transfer: Benefits of playing MMORPGS towards enhancing IT managerial skills - Chohan, Faizan M.; Mohd Yusof, Shafiz Affendi (2014)
This study is concerned with the positive effects, learnability and real-life skill knowledge transfer of commercial off-the-shelf video games.While extensive studies being carried out in exploring skill transfer from virtual world to real world in domains such as education and healthcare, it is felt that further study is needed to explore if these skills can be applied towards enhancing IT managerial skills.The focus of this study is on Massively Multiplayer Online Role Playing Games (MMORPGs).MMORPGs are 3D online virtual worlds that allow players to interact with millions of other players through avatars.On the other hand, IT managerial skills definitions are determined by referencing the Skills Framework for Information Age (SFIA), a comprehensive ICT competency framework of nearly 100 IT professional skills.Thus this study is framed around answering the following question: What are the perceptions on the benefits of playing MMORPGs towards enhancing IT managerial skills?